Pemanfaatan Sistem Informasi untuk Meningkatkan Efektivitas Layanan Posyandu Restu Ibu - Amir, Faisal; Fadilillah, Fadli; Riyanto, Riyanto; Oriyasmi, Fadhilah; Hasibuan, Rajimar Suhal; Putra, Kevin Dwi (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2025)
Administrative tasks at Posyandu Restu Ibu are still managed manually, including the recording of child growth data, maternal health, and activity reports. This condition often results in data management difficulties and delayed information access. To overcome these challenges, a web-based information system was designed and implemented to assist cadres in recording and managing Posyandu activities more efficiently. The system provides features for recording toddlers and pregnant women data, scheduling services, and generating reports in real time. The implementation shows that the system improves data accuracy, speeds up information retrieval, and simplifies the preparation of monthly reports. By utilizing this technology, Posyandu Restu Ibu can deliver services that are more structured and responsive to community needs